Antiviral carboxylic acids and naphthoquinones from the stems of Rhinacanthus nasutus - Benchaluk Thongchuai (2018)
© 2015 Elsevier Ltd. All rights reserved. Three new carboxylic acids, rhinacanthinic acids A-C (1-3), together with six known naphthoquinones and one known δ-lactone were isolated from the stems of Rhinacanthus nasutus. The structures of the isolated compounds were elucidated based on spectroscopic evidence. Their antiviral activity against herpes simplex virus type-2 (HSV-2) and cytotoxicity were examined.